2003
DOI: 10.1074/jbc.m207596200
|View full text |Cite
|
Sign up to set email alerts
|

E2F Proteins Regulate MYCN Expression in Neuroblastomas

Abstract: Amplification of the MYCN gene, resulting in overexpression of MYCN, distinguishes a subset of neuroblastomas with poor prognosis. The transcription factors driving MYCN expression in neuroblastomas are unknown. In transient-transfection assays, E2F-1, E2F-2, and E2F-3 activate a MYCN reporter construct dependent on the presence of several putative E2F-binding sites. Using chromatin immunoprecipitation, we show that E2F-1, E2F-2, and E2F-3 bind to the proximal MYCN promoter in vivo, specifically in neuroblasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 48 publications
6
75
0
Order By: Relevance
“…The transcription factors known to regulate Bmi1 expression are sonic hedgehogactivated Gli1 protein (Leung et al, 2004), E2F family members (Nowak et al, 2006), zinc-finger transcription factor SALL4 (Yang J et al, 2007) and c-Myc (Guney et al, 2006). As E2F1 regulates NB tumorigenesis through direct binding to MYCN promoter and its activation, E2F may regulate NB cells using complicated MYCN, MYCN/Bmi1 and Bmi1 regulation mechanisms (Strieder and Lutz, 2003;Kramps et al, 2004). Abbreviation: NB, neuroblastoma.…”
Section: Regulation Of Bmi1 Gene Transcriptionmentioning
confidence: 99%
“…The transcription factors known to regulate Bmi1 expression are sonic hedgehogactivated Gli1 protein (Leung et al, 2004), E2F family members (Nowak et al, 2006), zinc-finger transcription factor SALL4 (Yang J et al, 2007) and c-Myc (Guney et al, 2006). As E2F1 regulates NB tumorigenesis through direct binding to MYCN promoter and its activation, E2F may regulate NB cells using complicated MYCN, MYCN/Bmi1 and Bmi1 regulation mechanisms (Strieder and Lutz, 2003;Kramps et al, 2004). Abbreviation: NB, neuroblastoma.…”
Section: Regulation Of Bmi1 Gene Transcriptionmentioning
confidence: 99%
“…Chromatin Immunoprecipitation Assay-The protocol for chromatin immunoprecipitation and the primers used have been described (14). PCR products were either visualized on an agarose gel or directly quantified on an ABI7000 using SYBR Green.…”
Section: Methodsmentioning
confidence: 99%
“…We previously showed that E2F-1 activates the MYCN promoter in neuroblastoma cells (14). Co-expression of either Sp1 or the long isoform of Sp3 with limiting amounts of E2F-1 resulted in synergistic activation of the MYCN promoter (Fig.…”
Section: Sp1 and Sp3 Activate The Mycn Promoter And Synergize With E2mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the collaborative activity between MYCN and BMI1 may be switched on by a single initiating event, as deregulated E2F1 activity, which is a characteristic lesion in highly proliferative neuroblastoma tumors, 95 is capable of directly driving the expression of both oncogenes. 81,96 The role of BMI1 in neuroblastoma pathogenesis seems not to be limited to MYCN-amplified tumors, as BMI1 is also expressed and required for tumorigenicity in neuroblastoma cells with a normal copy number of MYCN. 82 In line with the requirement Inactivation of p53 in neuroblastoma T Van Maerken et al of BMI1 activity in self-renewal of neural stem cells, it has been argued that BMI1 may be of critical importance for the maintenance of neuroblastoma stem cells by regulating clonogenic self-renewal and multilineage differentiation, offering an attractive target for therapeutic intervention.…”
Section: Transactivation Of Mdm2 Expression By Mycnmentioning
confidence: 99%